Effectiveness of the Literacy Program in Building A Reading Culture at School - Irmayanti, Susi; Mustiningsih, Mustiningsih (Universitas Negeri Malang, 2025)
In the digital era, literacy skills are crucial for accessing and processing information. However, low reading interest among students remains a challenge, often due to limited resources and unsupportive environments. School literacy programmes aim to address these issues by promoting enjoyable and relevant reading activities. This study evaluates the effectiveness of these programmes in fostering a reading culture, enhancing comprehension, and developing critical thinking skills. The findings are expected to guide improvements in literacy programmes, strengthening reading culture in schools. This study used a literature study approach, gathering secondary data from scientific articles, books, and policy reports focused on literacy programmes in Indonesian schools. Data collection involved a systematic review of literature published within the last seven years. The collected data was analyzed descriptively through content analysis to identify patterns and strategies in literacy programme implementation. This analysis provided insights into the effectiveness of these programmes, their impact on students, and the factors that support or hinder programme success, as well as potential alternative solutions. Program literasi di sekolah efektif meningkatkan minat baca dan keterampilan berpikir kritis siswa, sekaligus membangun budaya membaca yang konsisten. Dukungan sekolah, ketersediaan fasilitas, peran guru, serta kolaborasi dengan orang tua dan komunitas menjadi faktor penting dalam keberhasilan program. Meski ada tantangan seperti keterbatasan sumber daya, hal ini bisa diatasi dengan fasilitas yang nyaman, kegiatan literasi yang menarik, serta monitoring berkala. Dukungan penuh dari lingkungan sekolah dan keluarga sangat menentukan demi keberlanjutan program literasi ini..